1972
DOI: 10.1302/0301-620x.54b1.103
|View full text |Cite
|
Sign up to set email alerts
|

The Semitendinosus Tenodesis for Recurrent Dislocation of the Patella

Abstract: Les luxations de Ia rotule en dehors des luxations trauniatiques r#{233}centes. Revue d'Orthop#{233}die, 36, 181. MARZIANI, R. (1930): Sulla lussazione della rotula e sul suo trattamento operativo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
7

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 5 publications
1
55
0
7
Order By: Relevance
“…More recently, Letts et al [38] presented a series of 26 knees with 82% good to excellent results with a recurrence rate of 8%. This study is similar to the results previously reported by Baker et al [2].…”
Section: Compare Two Techniques In This Study and Other Techniquessupporting
confidence: 94%
See 4 more Smart Citations
“…More recently, Letts et al [38] presented a series of 26 knees with 82% good to excellent results with a recurrence rate of 8%. This study is similar to the results previously reported by Baker et al [2].…”
Section: Compare Two Techniques In This Study and Other Techniquessupporting
confidence: 94%
“…If compare excellent and good result of Baker technique [2] and two techniques in this study shown our technique were better than Baker technique (p valuate > 0.0085) (see Table 5). Bensahel et al [16] performing operation for unstable patella in children with postoperative good result in 85%.…”
Section: Compare Two Techniques In This Study and Other Techniquesmentioning
confidence: 54%
See 3 more Smart Citations